Analisa RasioKeuangan (RasioProfitabilitas Dan RasioLikuiditas) UntukMengukur Kinerja Keuangan Perusahaan Pada Indotrans Tour & Travel Surabaya - Iswandi, Dinda; Mulyati, Diana; Maruto, IGN Anom (Jurnal Dinamika Administrasi Bisnis, 2021)
AbstractIn general the purpose of the company was established to gain profit. Profit can be obtained with good company performance. Performance is used as a measuring instrument in assessing the success of a company. It can also be used for consideration in making decisions and planning for future sales. In principle, the better the performance of a company, the better the achievement of the company in making profit. The purpose of this research is to know the ratio of profitability and liquidity to the measurement of the financial performance of the company Indotrans Tour & Travel Surabaya, and can provide improvement recommendations to the problems that exist in the company to improve the company's financial performance.This research is a descriptive study with a quantitative approach, a method to analyze the financial statements of losses/profits and balances within a period of a company, which will then be analyzed using the foundation of theories and formulas that correspond to the problems being researched by researchers. The object of this research is the financial statement in the form of income statement and balance of Indotrans Tour & Travel Surabaya period 2017-2019.The results revealed that the calculation of profitability ratio, liquidity ratio, and economic value added fluctuating annually. This indicates that the company's condition is less stable, as the company's financial statements are fluctuating and some of the report's posts are decreasing making the ratio decrease. However, based on the calculation of economic value added, it is seen that the company succeeded in adding value to the company, but according to the researchers magnitude economic value added Indotrans Tour & Travel Surabaya can not be said big. Therefore, the company needs to harvest the financial better again.Keywords : Profitability, Liquidity, Corporate Financial Performance